Analysis of Marketing Strategies of Qardh Products Containing Fat in Increasing the Number of Customer at Syariah Bank Indonesia KCP Medan Aksara - Ritonga, Melisa Ananda Putri; Inayah, Nurul; Daulay, Aqwa Naser (Ilomata International Journal of Management, 2024)
In facing this dynamic, the BSI KCP Medan Aksara branch in Medan City has an undeniable role. As one of the existing BSI branches, BSI KCP Medan Aksara is required to not only provide quality sharia banking products and services, but also to become a forum for meeting customer needs by prioritizing sharia principles. Gold-backed Qardh products not only meet customers' financial needs, but also provide solutions that are in line with their religious beliefs and values. This research uses a qualitative research method with an analysis instrument using SWOT which aims to identify factors that influence the effectiveness of marketing strategies, as well as understanding how banks can overcome existing challenges. With an interview instrument and involving 3 respondents. Based on the research results, this research produces that Based on the SWOT results it can be concluded that the strategy chosen by Bank Syariah Indonesia KCP Medan Aksara is SO (Strength and Opportunities) by utilizing a wide branch network to hold education and seminars about Gold Backed Qardh products, optimizing technology sophisticated information to develop mobile applications and online platforms, train sales forces to provide education and consultation to the upper middle market segment, develop strategic partnerships with other sharia financial institutions to develop new products and services, use social media for intensive promotional campaigns about products Gold Backed Qardh. Being in quadrant I position shows a very favorable situation for the company to carry out an aggressive/growth strategy.